The Use of Candida pulcherrima in Combination with Saccharomyces cerevisiae for the Production of Chenin blanc Wine - Jolly, N.P.; Augustyn, O.P.H.; Pretorius, I.S. (South African Journal of Enology and Viticulture, 2017)
Wine fermentations are conducted by naturally occurring or selected industrial wine yeast strains of Saccharomyces cerevisiae. However, non-Saccharomyces yeasts also occur naturally in fermenting grape musts, especially in the initial stages of the fermentation. It has been speculated that these yeasts can contribute to the overall characteristics of the wine. Generally, it is accepted that Kloeckera apiculata is the predominant non-Saccharomyces yeast species in grape must. However, it was shown previously that Candida pulcherrima was the predominant non-Saccharomyces yeast species in a grape must after sedimentation and prior to inoculation with commercial wine yeast. Subsequently, this yeast was investigated in laboratory and small-scale wine fermentations of Chenin blanc wine. As it could not ferment grape juice to dryness on its own, it was used in combination with a S. cerevisiae wine yeast strain. The effect of SO2, di-ammonium phosphate (DAP), pH and temperature on the growth of C. pulcherrima was also investigated. In combined fermentations, no change in overall fermentation rate or standard wine chemical analyses could be observed in comparison to a control S. cerevisiae fermentation. However, wine production in three consecutive years showed that the wine produced by the combined fermentation was of higher quality than that produced by the S. cerevisiae only.